Pendampingan Anak Zaman Now Secara Edukatif Melalui Praktik Ubudiyah - Ahmad Zaki Musthofa; Muh. Hasyim Rosyidi; Nurul Indana; Ali Mustofa (Yayasan Mutiara Hati Moeslem, 2026)
The educational mentoring activity for today's children through Ubudiyah practices is carried out as a form of community service in understanding religion. This activity aims to improve the understanding of children at the Nasrul Ummah Mosque in carrying out ubudiyah practices, especially the importance of the correct way of ablution and prayer according to the guidance of the Prophet Muhammad. The program targets children at the Nasrul Ummah Mosque aged 5–14 years who are still in the stage of forming character and worship habits. The method of implementing the activity includes initial observation, socialization, connecting worship practices (Ubudiyah) with the challenges and daily lifestyles of today's children. The results of the program implementation show an increase in the discipline and abilities of students in worship practices, as well as a growing awareness of the importance of regular worship. In addition, this activity has a positive impact on society in the order of children in worship. Thus, this program contributes to forming a generation of today's children who have character, discipline, and noble character in worship